Macromolecular Crowding Meets Tissue Engineering by Self‐Assembly: A Paradigm Shift in Regenerative Medicine. (6th February 2014) - Satyam, Abhigyan; Kumar, Pramod; Fan, Xingliang; Gorelov, Alexander; Rochev, Yury; Joshi, Lokesh; Peinado, Héctor; Lyden, David; Thomas, Benjamin; Rodriguez, Brian; Raghunath, Michael; Pandit, Abhay; et al.
<x xml:space="preserve">Abstract</x> MMC, the addition of inert polydispersed macromolecules in the culture media, effectively emulates the dense in vivo extracellular space, resulting in amplified deposition of ECM in vitro and subsequent production of cohesive, ECM‐rich living substitutes. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>